Occurrence of classes I and II integrons in Enterobacteriaceae collected from Zagazig University Hospitals, Egypt - Malek, Mai; Amer, Fatma A.; Allam, Ayman; El-Sokkary, Rehab; Gheith, Tarek; Arafa, Mohamed (Frontiers in Microbiology, 2015)
Integrons are genetic units characterized by ability to capture and incorporate gene cassettes that can contribute to emergence and transfer of antibiotic resistance between bacteria. The objectives of this study were: 1) to investigate the presence and distribution of class I and class II integrons and the characteristics of the gene cassettes they carry in Enterobacteriaceae isolated from nosocomial infections at a University Hospital in Egypt, 2) to determine their impact on resistance, and 3) to identify risk factors for the existence of integrons. Full clinical history and relevant samples were collected from 118 inpatients. Samples were processed, identified and tested for antibiotic susceptibilities. Integrons were detected by polymerase chain reaction (PCR) and were characterized into class I or II by restriction fragment length polymorphism (RFLP). Integron +ve isolates were subjected to another PCR to detect gene cassette, followed by gene cassette sequencing. Risk factors were concluded by statistical analysis using Fischer Exact Test. Seventy-six Enterobacteriaceae isolates were recognized, 41 of them (53.9 %) were integron-positive. Thirty-nine strains carried class I and 2 strains carried class II integrons. Integrons had gene cassettes encoding different combinations and types of resistance determinants. Interestingly, blaOXA129 gene was found and ereA gene was carried on class I integrons. The same determinants were carried within isolates of the same species as well as isolates of different species. The presence of integron was significantly associated with multidrug resistance. Risk factors for integron positivity were trauma, hospitalization for more than 7 days, and ICU admission. We conclude that integrons carrying gene cassettes encoding antibiotic resistance are significantly present among Enterobacteriaceae causing nosocomial infection in our hospital. Identifying risk factors can help in developing sound combating strategies.